Teaching global English in a local context: teachers' realities in Mongolian public schools. Issue 2 (3rd April 2022) - Marav, Daariimaa; Podorova, Anna; Yadamsuren, Odtsetseg; Bishkhorloo, Boldsuren
ABSTRACT: English has been increasingly used for global communication purposes, and educational systems in many countries have responded by prioritizing English language education over teaching and learning of other foreign languages. In Mongolia, the growing popularity of English resulted in the nationwide programmes on English Language Education that required skilled English language teachers to engage students in meaningful language learning opportunities. To date, no empirical studies on the impact of the new English language curriculum on Mongolian secondary teachers' beliefs and practices have been reported in the literature. This study aims to address this gap by exploring secondary school teachers' perceptions about the successes and challenges of teaching a global language in a local context. The findings suggest that Mongolian public school teachers face multiple challenges, including frequent curriculum and textbook changes, large class sizes, inadequate facilities and insufficient resources. At the same time, the findings of this study shed light on positive developments in the field of secondary EFL teaching in Mongolia. It is hoped that this study will inform policymakers and other stakeholders about on-the-ground understandings and implementation of educational reforms, as well as provide English teachers in similar contexts with strategies required to maintain effective EFL teaching practices.